Migrant families' access to ECEC and family policies: The Australian and Italian case compared - Naldini, Manuela; Adamson, Elizabeth; Hamilton, Myra (Frontiers in Sociology, 2022)
This paper analyses in a comparative perspective the degree of convergence in migrant families’ access to early childhood education and care (ECEC) and work/family policies in two different welfare state regimes: Italy and in Australia. Using a framework based on the concept of conditionality (Clasen and Clegg, 2007; Shutes, 2016) – or the notion that access to support is conditional and based on an individual’s personal and familial characteristics, circumstances or behaviours – the analysis examines the extent to which policies designed to support families with young children are accessible to migrant families. It argues that access to ECEC and family policies is restricted in both Italy and Australia according to a series of conditions, but that these conditions apply differently to people of different migrant statuses. In doing so the paper aims to improve our understanding of how welfare states respond to needs associated with migration for children and families and the extent to which they tend to converge.